MNG-3 STRATIFICATION OF TUMOR GROWTH BY RISK FACTORS AND PREDICTED TUMOR VOLUME CURVES FOR SUPRATENTORIAL MENINGIOMAS. (3rd December 2022) - Hirayama, Ryuichi; Yamada, Shuhei; Iwata, Takamitsu; Utsugi, Reina; Tachi, Tetsuro; Kuroda, Hideki; Kijima, Noriyuki; Okita, Yoshiko; Kagawa, Naoki; Kishima, Haruhiko
Abstract: Background: The natural history of meningiomas is still unclear, and no guidelines have been established based on objective indices regarding the necessity and timing of therapeutic intervention.Objective: We attempted to provide statistics on the characteristics of tumor volume change, stratify tumor growth by risk factors, and generate a predictive tumor volume curve based on the statistics, with the aim of describing the natural history of meningiomas. Methods: 313 cases were included in the study, with the origin of meningioma being the circumflex and parasagittal sinus areas and the cerebral sickle region, and with multiple MRI scans performed at intervals of at least 3 months. Relative growth rate (RGR) and annual volume change (AVC) were calculated by measuring tumor volume, and the patients were classified into three groups according to the combination of gender, age, and MRI T2WI signal intensity, and compared. Results: The median RGR and AVC of the entire cohort were 6.1% and 0.20 cm3/year, respectively, and there were significant differences between groups in gender (p=0.018) and MRI T2WI (p < 0.001) for RGR and tumor location (p=0.025) and initial tumor volume (p < 0.001)for AVC. The median RGR and AVC in the classification were 17.5% and 1.05 cm3/year for the very high growth group, 8.2% and 0.33 cm3/year for the high growth group, and 3.4% and 0.04 cm3/year for the low growth group, showing significant differences between the groups (p < 0.001). The predicted tumor volume curve showed an average 2.24-fold or 5.24 cm3 increase in volume over 5 years in the very high-growth group, while little tumor volume change was observed in the low-growth group. Conclusion: The combination of growth risk factors allowed stratification of tumor growth and provided a predictive tumor volume curve for each county. The results may assist in the treatment of meningiomas.